Pendistribusian Pupuk Bersubsidi dengan Acuan Rencana Definitif Kebutuhan Kelompok (RDKK) Perspektif Etika Bisnis - Sugiono Sugiono; Siti Faridatul Gufroniah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Subsidized fertilizers are goods under supervision whose procurement and distribution receive subsidies from the Government. Subsidized fertilizers are used to meet the needs of farmer groups and farmers in the agricultural sector which is regulated through the Definitive Plan for Group Needs (RDKK). RDKK is the calculation of the plan for subsidized fertilizer needs prepared by farmer groups based on the use of fertilizers that are higher or less than the recommendation to reduce the efficiency and effectiveness of fertilizer use. Based on the problem formulation, this study aims to explore the distribution channel system for subsidized fertilizers in Cumedak Village, Sumberjambe District, Jember Regency according to the perspective of business ethics. This research uses a qualitative approach with a case study type in Cumedak Village, Sumberjambe District, Jember Regency. The results of the study show that basically subsidized fertilizers have the potential to improve people's welfare. However, the underlying problem that actually occurs is that the distribution of subsidized fertilizers tends to be lower than the distribution of non-subsidized fertilizers. Keywords: Subsidized Fertilizer, RDKK, Business Ethics